SEJARAH PERKEMBANGAN HUKUM WARIS DI INDONESIA - Iim Fahimah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
In this discussion the development of inheritance law was stated, from the time before  colonialism until  the time of independence. In the development of inheritance law before  the colonial period, the empire and  the sultanate applied inheritance law as a living law in the  community as well as a culture of Indonesian law in its time.  When  the Dutch East Indies government arrived, Indonesia had  implemented Islamic religious law, which  then continued and recognized its legal authority, Van den Berg conceptualized Staatsblat 1882 Number 152 which contained provisions for indigenous people or colonized people, religious laws must be applied in his environment. Snouck Hoergronje, advisor to the  Dutch East Indies Government, initiated the  receptie theory of Islamic issues  and  domestic children who pro- posed “Islam  can apply if it has been perceived by customary law”, so adat  is what determines the existence or absence of Islamic law. Furthermore, at the  time  of independence Indonesian Islamic law experts tried  to make  Islamic law a national law, with the effort of national seminars in the formation of law, Islamic law was made as one of the sources in addition to European law and Customary law